Budget gives short shrift to agriculture - Pathak, Himanshu; Kumar, Anjani (Kasturi & Sons, 2022)
This year’s Budget had four broad themes — (i) PM Gati Shakti, (ii) Inclusive Development, (iii) Productivity Enhancement & Investment, Sunrise Opportunities, Energy Transition, and Climate Action and (iv) Financing of Investments.